Genetic investigation of Irish ancestry and surname history - McEvoy, Brian Patrick (Trinity College (Dublin, Ireland). Department of Genetics, 2005)
Several genetic systems were employed in this study to investigate Ireland’s pre-history and history. Initially Irish origins were examined using mtDNA sequence variation in 200 new samples coupled with an extensive novel analysis of pre-existing European mtDNA, Y chromosome and autosomal diversity. The same prominent trend is recorded in loci with different inheritance modes and indicates a shared genetic ancestry among the people of the European Atlantic Façade. The origins of this probably lie in the post glacial recolonisation of Western Europe and Ireland from an Iberian Ice age refugium and its preservation precludes complete or substantial population replacement by central European Celtic invaders during the Iron Age. Additional examination of longitudinal east-west Irish autosomal diversity using classical genes and 380 STRs detected little evidence of the strong intra-Ireland genetic differentiation observed in the Y chromosome. This is in agreement with mtDNA and potentially points to the importance of male-specific behaviours, rather than preferential East-coast migration, in generating the Y chromosome pattern. Next, the extent of patrilineal coinheritance of Y chromosomes and Irish surnames was explored and then used to investigate the specific origins and histories of several surnames. Analysis of Y chromosome diversity in 1105 men using a combination of fast evolving STR and stable UEP markers, in both local and general Irish contexts, demonstrates that Irish surnames collectively reflect real and recent shared paternal ancestry. The extent of this varies between surnames reflecting basic differences in the number of early founders. Furthermore, modern surname populations are invariably a mixture of numerous paternal ancestries of varying legacy, indicating complex and continuously evolving post-foundation histories. While these results are in broad agreement with historical accounts, there is nonetheless a valuable role for a molecular Y chromosome approach in the elucidation of individual surname history. In a variation on this approach, Y chromosome diversity in 47 Irish men with a putative Viking/Norse surname origin was used to explore the nature and extent of Viking settlement in Ireland. Extensive admixture analysis detected little or no Scandinavian ancestry indicating a substantial Norse cultural impact in the absence of a large number of Scandinavian migrants; an observation perhaps best explained by an elite dominance model of Viking settlement in Ireland.
Keywords: Genetics, Ph.D.; Ph.D. Trinity College Dublin